Autosomal Dominant Polycystic Kidney Disease: From Pathophysiology of Cystogenesis to Advances in the Treatment - Reiterová, Jana; Tesař, Vladimír (International journal of molecular sciences, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic renal disease, with an estimated prevalence between 1:1000 and 1:2500. It is mostly caused by mutations of the PKD1 and PKD2 genes encoding polycystin 1 (PC1) and polycystin 2 (PC2) that regulate cellular processes such as fluid transport, differentiation, proliferation, apoptosis and cell adhesion. Reduction of calcium ions and induction of cyclic adenosine monophosphate (sAMP) promote cyst enlargement by transepithelial fluid secretion and cell proliferation. Abnormal activation of MAPK/ERK pathway, dysregulated signaling of heterotrimeric G proteins, mTOR, phosphoinositide 3-kinase, AMPK, JAK/STAT activator of transcription and nuclear factor kB (NF-kB) are involved in cystogenesis. Another feature of cystic tissue is increased extracellular production and recruitment of inflammatory cells and abnormal connections among cells. Moreover, metabolic alterations in cystic cells including defective glucose metabolism, impaired beta-oxidation and abnormal mitochondrial activity were shown to be associated with cyst expansion. Although tolvaptan has been recently approved as a drug that slows ADPKD progression, some patients do not tolerate tolvaptan because of frequent aquaretic. The advances in the knowledge of multiple molecular pathways involved in cystogenesis led to the development of animal and cellular studies, followed by the development of several ongoing randomized controlled trials with promising drugs. Our review is aimed at pathophysiological mechanisms in cystogenesis in connection with the most promising drugs in animal and clinical studies.
Keywords: Apoptosis; cysty; Phosphatidylinositol 3-Kinases; fosfatidylinositol-3-kinasy; apoptóza; tolvaptan; lidé; Animals; Polycystic Kidney, Autosomal Dominant; Tolvaptan; Cysts; zvířata; polycystické ledviny autozomálně dominantní; Humans